VO₂Max Differences Between Smokers and Non-Smokers Using the Rockport Test Among Male Staff - Hanum Salsabilah; Nurhikmawati; Rezky Pratiwi L. Basri; Wisudawan; Edward Pandu Wiriansya (Fakultas Kedokteran Universitas Malikussaleh, 2026)
Smoking is a global health problem that remains a serious concern, including in Indonesia, which has the highest smoking prevalence in the ASEAN region. Exposure to harmful substances in cigarettes, such as nicotine, tar, and carbon monoxide, can impair the cardiovascular and respiratory systems, leading to decreased oxygen saturation and physical endurance. One important indicator of cardiorespiratory fitness is VO₂Max, which reflects the body’s maximal ability to absorb and utilize oxygen during physical activity. Smoking habits and a physically inactive lifestyle are known to contribute to decreased VO₂Max and an increased risk of chronic diseases. Therefore, this study aimed to describe the VO₂Max values of smokers and non-smokers among staff at SMAN 11 Pinrang using the Rockport Walking Test. This study employed a descriptive quantitative design with a cross-sectional approach. The subjects were male staff members of SMAN 11 Pinrang classified as smokers and non-smokers. The results showed that the mean VO₂Max value of smoking male staff was 42.36 ± 6.30 ml/kg/min, categorized as Fair Good. Meanwhile, the mean VO₂Max value of non-smoking male staff was 47.46 ± 4.18 ml/kg/min, categorized as Good–Excellent. There was a significant difference in VO₂Max values between smokers and non-smokers (p = 0.007), with the non-smoking group demonstrating better aerobic capacity. In conclusion, non-smoking male staff had higher VO₂Max values than smokers, and this difference was statistically significant, indicating that smoking harms cardiorespiratory fitness.